2010
DOI: 10.1111/j.1538-7836.2010.03863.x
|View full text |Cite
|
Sign up to set email alerts
|

von Willebrand factor propeptide and the occurrence of a first ischemic stroke

Abstract: von Willebrand factor propeptide and the occurrence of a first ischemic stroke propeptide and the occurrence of a first ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Interestingly, there is one recent study in which both VWF antigen and VWF propeptide were investigated in two casecontrol samples of patients with IS or transient ischemic attacks (n = 204 and n = 342) [11]. The results suggest that increased von Willebrand factor in ischemic stroke subtypes 279 secretion of VWF from the endothelium is an important mechanism underlying the association between total VWF levels and IS, but a lower clearance of VWF may also contribute.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, there is one recent study in which both VWF antigen and VWF propeptide were investigated in two casecontrol samples of patients with IS or transient ischemic attacks (n = 204 and n = 342) [11]. The results suggest that increased von Willebrand factor in ischemic stroke subtypes 279 secretion of VWF from the endothelium is an important mechanism underlying the association between total VWF levels and IS, but a lower clearance of VWF may also contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, blood sampling was standardized and performed at two time points, whereof one was in the chronic phase. Only a few previous studies [5][6][7]11,17] have examined VWF levels at more than one well-defined time-point. There are also some limitations that should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…75 Endothelial activation, as indicated by an elevated VWFpp level has been implicated in chronic renal failure, aortic stenosis, ischemic stroke, sepsis, meningococcal disease, dengue, systemic sclerosis, sickle cell disease, HELLP syndrome, and asthma. [78][79][80][81][82][83][84][85][86] In addition to utility in identifying endothelial activation, VWFpp and VWF may also be used in a similar manner to identify platelet activation. 87 In some clinical circumstances, an elevated VWFpp level may indicate activation of both platelets and endothelial cells.…”
Section: Assay Of Plasma Vwfpp: Clinical Utility Vascular Disorders Amentioning
confidence: 99%
“…It is also considered as an emerging target in cerebral ischaemia (Varga-Szabo et al, 2008;De Meyer et al, 2012). Investigations of independent case-control studies indicated the association between high vWF levels and the occurrence of a first ischaemic stroke and mortality in humans (Van Schie et al, 2010). Protection of vWF-deficient mice from ischaemic stroke injury (Kleinschnitz et al, 2009), together with enlarged infarct size in ADAMTS13-deficient mice (Fujioka et al, 2010;Khan et al, 2012), suggests an important role of vWF in ischaemic stroke.…”
Section: Figurementioning
confidence: 99%